Weighting, suitability, obedience and discretion make judges in Colombia see the law backwards - Marín Gil, Johnny (DIXI, 2023)
Title and scope: The conventionality control established by the Inter-American Court of Human Rights must be understood as the way in which the State addresses its obligations regarding the respect and guarantee of human rights. It is a mechanism for protection and for making fundamental rights effective and inherent to the human being, enshrined in the various sources of Public International Law, mainly in international treaties. Characteristics: Colombia, despite having a Constitution that guarantees and is based on human dignity, applies this mechanism at the discretion, almost at the judges’ will. Findings: A State Party has the legal duty to adopt the necessary measures to fulfill its obligations in accordance with the treaty, whether executive, legislative, judicial, or of another nature, for the protection of the concerned right. The three branches of government in Colombia do not recognize and apply that procedural requirements are indispensable for the integration of the process and for issuing the judgment that addresses the substance of the matter, essentially due to lack of knowledge on these topics. Conclusions: The Colombian Council of State, the Supreme Court of Justice, and the Constitutional Court, when issuing their rulings, do not effectively apply the conventionality control of the Inter-American Court of Human Rights.